Economic Inequality, the Digital Divide, and Remote Learning During COVID-19. Issue 1 (March 2022) - Francis, Dania V.; Weller, Christian E.
Wealth and education establish a cycle of intergenerational inequality. Wealthier households can provide more educational opportunities for their children, who then will have more chances to build wealth for themselves. The digital divide may have emerged as a key reinforcing mechanism of education through wealth and of future wealth through education during the pandemic. The intergenerational transmission of racial wealth inequality likely played out at rapid speed during the pandemic. We analyze the link between wealth, reliable internet and electronic device availability, remote learning time, race, and ethnicity, using the U.S. Census Bureau's Household Pulse Survey. We conclude that Black and Hispanic/Latinx households have less reliable internet and devices available. This goes along with fewer hours children spend on remote learning. The lack of internet and devices correlates with less wealth, as reflected in lower homeownership rates and greater housing instability. Black and Hispanic/Latinx households, in particular, are more likely to be renters and face housing instability.